Anticipatory Environmental (Hi)Stories from Antiquity to the Anthropocene - Schliephake, Christopher; Zemanek, Evi (Lexington Books, 2023)
Anticipatory Environmental (Hi)Stories from Antiquity to the Anthropocene studies the interplay of environmental perception and the way societies throughout history have imagined the future state of “nature” and the environments in which coming generations would live. What sorts of knowledge were and are involved in outlining future environments? What kinds of texts and narrative strategies were and are developed and modified over time? How did and do scenarios and narratives of the past shape (hi)stories of the future? This book answers these questions from a diachronic as well as a cross-cultural perspective. By looking at a diverse range of historical evidence that transcends stereotypical utopian and dystopian visions and allows for nuanced insights beyond the dichotomous reservoir of pastoral motifs and apocalyptic narratives, the contributors illustrate the multifaceted character of environmental anticipation across the ages.